Driven Factors to Sustainable Paddy Farming Production in Malaysia - Zahari, Fadhilah; Othman, Zakirah; Abu, Noor Hidayah; Salleh, Nurul Azita (ExcelingTech, 2020)
As the organic food is rising in demand, there are several issues associated with its supply chain capabilities that deserve attention. These include the inadequate supply and increasing cost of rice production. The farmers play a significant role to ensure that the supply of organic products meets the demand of the market, hence understanding the motivation for their practices is crucial. This study explores the driving factors for farmers in sustainable paddy farming in Malaysia. The research is exploratory in nature, using interview and observation approaches. Three sustainability factors are focused in this study; namely the economic, social, and environmental dimensions. The results indicate that early exposure and knowledge, education and experience in sustainable agriculture are the driving force behind shifting attitudes towards sustainable agriculture and sustaining practices. The results of this study are expected to give awareness and motivate the farmers to embark on the alternative practices to sustainable rice cultivation, and also potentially help to optimize the abandoned land for productive farming in the rural areas